A study of the undrained shear strength of soft clay reinforced with 6mm and 8 mm diameter group of four bottom ash column - Nur Illani , Hayon (2014)
Soft clay that consists of low shear strength, low permeability and high compressibility characteristics will affect the stability and settlement of structures. Vertical granular column is one of the ground improvement techniques to improve strength of the soft soil. Bottom ash, as a residue of combustion of coal from coal power plants, has similar properties with sand. The weak soft soil is not suitable for structure construction. Hence, ground improvement is necessary to modify soil properties and increase shear strength of soft soil. Bottom ash is the by-product produced from the coal burning in power plant. The substantial amount of bottom ash disposed in the landfills generates serious environment pollution from time to timç. Hence, by using bottom ash as granular material in vertical granular column, the cost of construction is reduced and this could be one of the methods in achieving sustainable development in construction industry. The aim of this Final Year Project is to determine the improvement in the shear strength of soft clay after being reinforced with a group of four bottom ash columns. The first stage of study was to determine the physical and mechanical properties of the materials used, which were kaolin and bottom ash. The results shows that kaolin can be classified as clayey soil whereas for the bottom ash it has relatively similar characteristics to sand. At the second stage, remoulded samples of 50mm in diameter and 100mm in height soft kaolin clay with undrained shear strength were reinforced with group of bottom ash columns and subsequently tested under Unconfined Compression Test. The diameter of bottom ash column is 6nmi and 8mm, and the heights of column are 24mm, 36mm, 48mm and 68mm. The group columns have been arranged in square pattern. It can be concluded that the shear strength parameters were affected by the diameter and the height of the column. It can be concluded that the shear strength of soft clay could be improved by the installation of bottom ash columns. The presence of bottom ash column greatly improved the shear strength.